2013
DOI: 10.1016/j.fob.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Trim27‐deficient mice are susceptible to streptozotocin‐induced diabetes

Abstract: Tumor necrosis factor α (TNF-α) plays an important role in cell proliferation and apoptosis, and defects in TNF-α-induced apoptosis are associated with various diseases. TRIM27 is a tripartite motif (TRIM) protein containing RING finger, B-box, and coiled-coil domains. We recently reported that TRIM27 positively regulates TNF-α-induced apoptosis through deubiquitination of receptor-interacting protein 1 (RIP1). Multiple studies have suggested a link between TNF-α pathway and various diseases, such as diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, little evidence exists to indicate a linkage between Trim27 and disease. It was reported that Trim27-deficient mice are susceptible to STZ-induced diabetes, a mouse model of diabetes (Zaman et al, 2013b). Nevertheless, Trim27-mutation did not affect the dextran sodium sulphate (DSS)-induced colitis (Zaman et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little evidence exists to indicate a linkage between Trim27 and disease. It was reported that Trim27-deficient mice are susceptible to STZ-induced diabetes, a mouse model of diabetes (Zaman et al, 2013b). Nevertheless, Trim27-mutation did not affect the dextran sodium sulphate (DSS)-induced colitis (Zaman et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Trim27-deficient mice are susceptible to STZ-induced diabetes, a mouse model of diabetes (Zaman et al, 2013b). Nevertheless, Trim27-mutation did not affect the dextran sodium sulphate (DSS)-induced colitis (Zaman et al, 2013b). In addition, Trim27 was found to express in 62% of ovarian cancer patients and its positivity significantly correlated with drug resistance, suggesting that Trim27 could be a predictive marker for chemoresistance in ovarian cancer patients (Horio et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TRIM27 expression was elevated in the colon tissues of Crohn’s patients and in CD4 + T cells in the mesenteric lymph nodes of DSS-induced colitis mice ( 90 , 91 ). In a study by Zaman et al., Trim27 -/- mice were not sensitive to DSS-induced colitis, again implicating TRIM27 in the occurrence and development of IBD ( 92 ). Further research reported that the knockout of TRIM27 reduced DSS induced intestinal inflammation and inhibited tumorigenesis of CAC induced by AOM/DSS, mainly due to repression of signal transducer and activator of transcription 3 (STAT3) activation in hematopoietic cells ( 93 ).…”
Section: Ub E3 Ligases and Ibdmentioning
confidence: 99%
“…TRIM family proteins directly or indirectly acting as regulatory proteins are involved in the development of DM as well as diabetic complications. For instance, In TRIM27 deficiency islets, T‐cell infiltration and caspase‐3 cleavage signal were enhanced, and β cell mass was decreased, TRIM27‐deficient mice were predisposed to streptozotocin (STZ, a commonly used chemical inducer agent for diabetes model)‐induced DM (Zaman et al, 2013). TRIM32 was reported to mediate insulin resistance in the liver and skeletal muscle tissue via the inhibition of plakoglobin function in various catabolic states, including DM (Cohen et al, 2014).…”
Section: Trim Proteins In Dm and Diabetic Complicationsmentioning
confidence: 99%